A conceptual framework for exploring voluntary stewardship programs for land managers as a tool of New Environmental Governance. Issue 2 (3rd April 2019) - Lawson, Andrew
ABSTRACT: New Environmental Governance describes the widening over the past five decades of the range of public and private instruments, institutions, and actors available to govern the environment. But implementing New Environmental Governance arrangements has been difficult. This article responds to the call for more context-specific empirical investigations to better understand how New Environmental Governance institutions work in practice, by focusing on one tool in the expanded array of options – non-government voluntary stewardship programs for private land managers. The article applies a conceptual framework to three working examples of voluntary stewardship using a qualitative methodology to tease out key elements of their operations and unpack the relationship amongst three groups of actors – land managers who participate in the programs, organisations that manage the programs, and stakeholders who have an interest in private land stewardship. Important tensions emerge from the research, which revolve around the lack of strategic alignment between land managers' participation in programs and how stakeholders leverage their influence. These tensions limit the potential of stewardship programs as tools of New Environmental Governance arrangements.